Esterification of renewable levulinic acid to n-butyl levulinate over modified H-ZSM-5 - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Chemical Engineering & Technology, 2015)
The synthesis of n-butyl levulinate, one of the most important biodiesel additives, by catalytic esterification of biomass-derived levulinic acid (LA) with n-butanol over modified H-ZSM-5 (micro/meso-HZ-5) in a closed-batch system is reported for the first time. The optimization of the reaction conditions such as the reactant molar ratio, the catalyst loading, the reaction time and the temperature was performed in view to maximize the yield of n-butyl levulinate. Micro/meso-HZ-5 was found to be the most efficient catalyst, with 98% yield of n-butyl levulinate and a reusability for six cycles, which is higher than reported in the literature. A possible catalytic mechanism for the esterification reaction is also proposed. A second-order pseudo-homogeneous model with R-2 > 0.97 confirmed that the esterification reaction is performed in the kinetic regime due to the high activation energy of 23.84 kJ mol(-1).
Keywords: Esterification; kinetic model; levulinic acid; Micro/meso-HZ-5; n-Butyl levulinate